THE TECHNOLOGIES OF THE REALIZATION OF THE PRINCIPLES OF HISTORISM IN THE PROFESSIONAL ACTIVITY OF THE TEACHER OF MUSIC (Pedagogy of Higher and Secondary Education, 2007)
In the article says about the technologies of introducing the historical material into musical-educational process of the students of the comprehensive educational institutions on the basic of the personality oriented approach.
Keywords: historism; axiological analysis; comparativistics; individualization; independence; self-upbringing; humanist orientations